Adapting to E-Commerce: The Impact of Online Shopping on Traditional Retailers - Diego Cedro (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The rapid expansion of e-commerce has reshaped the retail landscape, significantly impacting traditional brick-and-mortar stores. This article examines the effects of online shopping growth on physical retailers, exploring key challenges such as declining foot traffic, increased competition, and shifting consumer expectations. It also highlights the strategies that traditional retailers are adopting to adapt to the digital transformation, including omnichannel approaches, enhanced in-store experiences, and the integration of technology and data analytics. The study emphasizes that while online shopping poses considerable challenges, it also offers new opportunities for physical stores to innovate and remain competitive in the evolving retail environment.